Design of Asphalt Mixing Plant Industry Information System - Pandowo, Hedi; Kusumaningrum, Dian; Nugroho, Sasmito Widi; Sari, Chanif Kurnia (Global Health Science Group, 2023)
Asphalt mixing plant is a production equipment that produces hot mix in the form of a mixture of asphalt with some aggregate materials used as road pavement materials. The asphalt mixing plant produces hot mix which must be at a certain temperature so that it does not harden and cannot be used for road pavement. The accuracy in the delivery time of the product to the location where it will be held determines the quality of the production after it is held on the road media. The existence of an information system is a tool for controlling production costs, in this case hotmix products produced from asphalt mixing plant machines are needed to monitor every production process from several departments that have been worked on so that data management can be done quickly and accurately. Seeing the existing problems, this research aims to design and build an industrial information system for the asphalt mixing plant at PT. Wasis by Nugraha. Tools used in making this system is Visual Basic. The application design method uses the ProtoTyping method. The results of this study are that with the design and construction of an industrial information system for the asphalt mixing plant at PT. Wasis Karya Nugraha received a very good category in the functional suitability aspect and a very appropriate predicate in the usability aspect in helping to overcome conventional system problems in the administration of raw material procurement to the production process, sending finished products to consumers and financial reporting which can be caused by human error.